1969
DOI: 10.1063/1.1658118
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat of α Al2O3 from 2 to 25 K

Abstract: The heat capacity of colorless synthetic sapphire (a Al20 a , corundum) has been measured from. 2 to 25.K. The data above 14 K can be expressed as C.= 1.755X1Q-'TB+1.905X1Q-'l]'6 ~J/K.g-atom. This equatlOn for C. gives 8 0 = 1035 K, in good agreement with the values calculated from elastic constant data. An extrapolation of these results to higher temperatures is consistent with other data. Below 14 K an anom~lous heatcapacity contribution appears which is about 1.5% of C. at its maximum. ~~e magnitu.de of ~~l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…We chose a 30 m thickness and 0.1 W K −1 m −1 thermal conductivity for the contact layer ͑silver paint͒. 36 Other physical values used in this calculation, such as heat capacity and thermal conductivity in each region, are taken from the literature; [36][37][38][39][40][41][42][43][44][45][46][47][48] these values are listed in the figure caption of Fig. 7.…”
Section: Frequency Test and Numerical Simulationsmentioning
confidence: 99%
“…We chose a 30 m thickness and 0.1 W K −1 m −1 thermal conductivity for the contact layer ͑silver paint͒. 36 Other physical values used in this calculation, such as heat capacity and thermal conductivity in each region, are taken from the literature; [36][37][38][39][40][41][42][43][44][45][46][47][48] these values are listed in the figure caption of Fig. 7.…”
Section: Frequency Test and Numerical Simulationsmentioning
confidence: 99%
“…From top to bottom, the longitudinal phonon velocity [8] the transverse phonon velocity [8] the atomic number density [25], and the Debye temperature [18,26] are important parameters used in DMM and PRL analysis. The lattice specific heat [25] and thermal conductivity [25] are used in fitting the thermal model [10] to the experimental data to determine h BD et al [14] observed thermal transport across the interface of two fcc lattice systems with varying degrees of mass and lattice mismatch using molecular dynamics simulations.…”
mentioning
confidence: 99%
“…The results for the heat capacity look to be reasonable compared to other data [2]. The loss tangent data is much higher than previous work [3,4].…”
Section: Resultsmentioning
confidence: 44%